The role of government policy on the performance of MSMEs in the creative industry: evidence from Jember Regency, East Java, Indonesia - Zainuri Zainuri; Mohammad Zeqi Yasin; Rachmania Nurul Fitri Amijaya; Regina Niken Wilantari; Sebastiana Vipindrartin (Cogent Economics & Finance)
Government policies, such as subsidies and loan interest discounts, have stimulated the performance of micro, small, and medium enterprises (MSMEs). This study aims to examine the influence of government policies through subsidies on MSMEs in the creative industry by employing primary data from MSMEs in Jember Regency, East Java, Indonesia. We captured that subsidies for MSMEs will positively affect economic performance, as proxied by turnover and profit, only if incorporated into the interest rate discount program. This finding is robust from different measurement strategies, suggesting that subsidy provision as a macroeconomic policy is unreliable if applied in Silos. In addition, social capital plays a vital role in developing businesses in the creative industry. It opens new market opportunities, provides a free source of learning, and allows for collaboration that reduces the economic transaction costs of managing businesses.